Effectiveness and safety of ustekinumab induction therapy for 103 patients with ulcerative colitis: a GETAID multicentre real‐world cohort study. Issue 11 (14th April 2020) - Amiot, Aurélien; Filippi, Jérôme; Abitbol, Vered; Cadiot, Guillaume; Laharie, David; Serrero, Melanie; Altwegg, Romain; Bouhnik, Yoram; Peyrin‐Biroulet, Laurent; Gilletta, Cyrielle; Roblin, Xavier; Pineton de Chambrun, Guillaume; et al.
Summary: Background: Phase III trials have demonstrated the efficacy and safety of ustekinumab in moderate‐to‐severe ulcerative colitis (UC), but few real‐world data are currently available. Aim: To assess short‐term effectiveness and safety of ustekinumab in patients with UC. Methods: From January to September 2019, all patients with UC treated with ustekinumab in 20 French GETAID centres were retrospectively included. The primary outcome was steroid‐free clinical remission (partial Mayo Clinic score ≤2) at weeks 12‐16 without a rectal bleeding subscore >1. Results: Among the 103 patients included, 70% had been previously exposed to ≥2 anti‐TNF agents and 85% to vedolizumab. At weeks 12‐16, steroid‐free clinical remission and clinical remission rates were 35.0% and 39.8% respectively; the absence of rectal bleeding with normal stool frequency was noted in 19.4% of patients. Two patients discontinued ustekinumab before the week 12‐16 visit and underwent surgery. In multivariable analysis, a partial Mayo Clinic score >6 at inclusion (18.6% vs 46.7%, P = 0.003) and a history of both exposure to anti‐TNF and vedolizumab therapies (27.3% vs 80.0%, P = 0.001) were negatively associated with steroid‐free clinical remission at weeks 12‐16. Adverse events occurred in 7.8% of patients and serious adverse events in 3.9% of patients. Conclusion: In a cohort of highly refractory patients with UC with multiple prior drug failures, ustekinumab provided steroid‐free clinical remission in one‐third of cases at weeks 12‐16. Clinical severity and previous use of anti‐TNF and vedolizumab therapies were associated with ustekinumab failure at weeks 12‐16.